Studi Sistem Informasi Monitoring Pembelian Material (Studi Kasus: K5-Project IKPT Toyo) - Zain, Abdul; Sutanto, Hari (Politeknik Negeri Ujung Pandang, 2017)
Kaltim-5 Factory is the biggest plant for Ammonia and Urea in Indonesia. Construction of this plant was executed by Consortium IKPT-TOYO. Along the construction stage, procurement for materials were absolutely needed, and Procurement Department IKPT-TOYO has responsibility to handle materials procures. System that currently used is still using Microsoft Excel by manual input for each steps beginning from inquiry stage, getting vendor quotation until PO issued. This method still has some problems occurred such as uncontrolled stock and material requisition, also inquiry sheet which can be easily lost. In order to support the completion of K5-Project that needs more materials, therefore it needs a system that can ease and also improve the work of Procurement Department. Based on this background, research study to resolve this problem is held. This system gives status information and it is integrated to the each control step smoothly. System development used on this program is SDLC with Waterfall model. Moreover, testing methods is using Black Box system. The design of this monitoring information system describes a work order application by using PHP Macromedia Dreamweaver 8, AppServ 2.10.2 as web server and MySQL as database. Having testing the application, the result of this study shows that the application is able to improve the data processing of material procurement with minimum of error and high accuracy.